Power losses evaluation of a bidirectional three-port DC-DC converter for hybrid electric system - Piris Botalla, Laureano Enrique (2014)
Power losses of a bidirectional three-port DC–DC converter to be used in hybrid electric systems as a function of the voltage conversion ratios and the output power are evaluated in this work. An analysis and characterization of the current on the switches into the whole converter operating range are presented. This analysis allows finding the semiconductor conduction intervals, necessary to calculate the power losses. Such losses are evaluated considering both switching and conduction semiconductor losses as well as those in the transformer. The variables used in this evaluation are voltage conversion ratios and transformer parameters like leakage inductances and turns ratios. Design considerations for the high frequency transformer that allow minimizing the total power losses are proposed. Simulation results are presented in order to validate the theoretical analysis.